Mass Casualties and Case Management. Issue 1 (January 2020) - Powell, Suzanne K.; Owen, Mindy
Abstract : The mass casualty statistics in the United States is numbing. Case managers must be prepared for potential disasters. This Editorial speaks to a case manager's personal experience and calls for others who have been through an experience with mass casualties, so all may better prepare: preparation is the antidote to panic .